Engaging the Underserved: A Process Model to Mobilize Rural Community Health Coalitions as Partners in Translational Research1. Issue 4 (19th May 2014) - Davis, Melinda M.; Aromaa, Susan; McGinnis, Paul B.; Ramsey, Katrina; Rollins, Nancy; Smith, Jamie; Beamer, Beth Ann; Buckley, David I.; Stange, Kurt C.; Fagnan, Lyle J.
Abstract Purpose Community engagement (CE) and community‐engaged research (CEnR) are increasingly recognized as critical elements in research translation. Process models to develop CEnR partnerships in rural and underserved communities are needed. Method Academic partners transformed four established Community Health Improvement Partnerships (CHIPs) into Community Health Improvement and Research Partnerships (CHIRPs). The intervention consisted of three elements: an academic‐community kickoff/orientation meeting, delivery of eight research training modules to CHIRP members, and local community‐based participatory research (CBPR) pilot studies addressing childhood obesity. We conducted a mixed methods analysis of pre‐/postsurveys, interviews, session evaluations, observational field notes, and attendance logs to evaluate intervention effectiveness and acceptability. Results Forty‐nine community members participated; most (78.7%) attended five or more research training sessions. Session quality and usefulness was high. Community members reported significant increases in their confidence for participating in all phases of research (e.g., formulating research questions, selecting research methods, writing manuscripts). All CHIRP groups successfully conducted CBPR pilot studies. Conclusions The CHIRP process builds on existing infrastructure in academic and community settings to foster CEnR. Brief research training and pilot studies around community‐identified health needs can enhance individual and organizational capacity to address health disparities in rural and underserved communities.